Gambaran Keluhan Telinga dan Letak Perforasi Membran Timpani pada Pasien dengan Otitis Media Supuratif Kronis - Tenty, Tenty; Nathaniel, Fernando; Wijaya, Dean Ascha; Firmansyah, Yohanes (Universitas Malahayati, 2023)
ABSTRACT Chronic Suppurative Otitis Media (CSOM) is a persistent inflammation of the middle ear. It is one of the most common ear infections worldwide, leading to hearing impairment and affecting people's quality of life. This study, conducted at Ciawi General Hospital in July 2023, is a cross-sectional investigation aiming to outline the ear-related complaints and the location of tympanic membrane perforations in patients with CSOM. The participants were selected based on total sampling criteria. The variables examined in this research include age, gender, perceived symptoms, and physical examination of both ears to identify the type of perforation in the tympanic membrane. The data is presented descriptively. Out of the 53 respondents, 56.6% were between 18 and 64 years old, with a higher proportion being female (52.8%). The most commonly reported symptoms by respondents (>50% of cases) with CSOM were a sense of fullness in the ear, hearing loss, tinnitus, otorrhea, and itching in the ear. According to the results of the physical examination, the most prevalent type of perforation was central perforation, occurring in 98.1% of cases, and 88.7% of cases showed ear discharge. The conclusion in this study is that CSOM has general symptoms accompanied by central perforation and symptoms of ear discharge. Keywords: Chronic Suppurative Otitis Media, Hearing Loss, Otorrhea, Perforation ABSTRAK Otitis media supuratif kronis (OMSK) merupakan suatu peradangan pada telinga tengah yang berlangsung kronis. OMSK termasuk infeksi telinga paling umum yang menyebabkan gangguan pendengaran dan mempengaruhi kualitas hidup seseorang di seluruh dunia. Penelitian potong lintang ini bertujuan untuk mengetahui gambaran keluhan telinga dan letak perforasi membran timpani pada pasien dengan OMSK di RSUD Ciawi yang dipilih sesuai kriteria secara total sampling pada periode waktu Juli 2023. Variabel yang digunakan dalam penelitian ini yaitu usia, jenis kelamin, gejala yang dirasakan, serta pemeriksaan fisik pada kedua telinga untuk melihat jenis perforasi pada membran timpani. Data disajikan dalam bentuk deskriptif. Dari 53 responden, 56,6% responden berusia 18 – 64 tahun dan didominasi oleh perempuan (52,8%). Gejala yang paling sering dirasakan oleh responden (>50% kasus) dengan OMSK adalah telinga terasa penuh, penurunan pendengaran, tinnitus, otorea, serta telinga yang terasa gatal. Berdasarkan hasil pemeriksaan fisik didapatkan bahwa jenis perforasi yang paling dominan adalah perforasi sentral pada 98,1% kasus dan terdapat sekret telinga pada 88,7% kasus. Kesimpulan pada penelitian ini adalah OMSK memiliki gejala yang umum disertai dengan perforasi sentral dan gejala sekret telinga Kata Kunci: Otitis Media Supurativa Kronis, Otorea, Penurunan Pendengaran, Perforasi